The analysis of lexical cohesion in students’ narrative writing - Dinda Tri Azhari; Susilawati Susilawati; Eline Rozaliya Winarto (Indonesian Journal of Education and Pedagogy, 2026)
Cohesion is a fundamental aspect that contributes to the coherence and clarity of a text. Among its types, lexical cohesion plays a key role in creating semantic connections through words that are related in meaning. Despite its importance, many EFL learners still lack awareness of how lexical cohesion operates in writing, particularly in narrative texts. This study aims to conduct a deeper analysis of the types and functions of lexical cohesion used by eighth-grade students in their narrative writing, highlighting how their use reflects their language proficiency. Employing a descriptive qualitative approach, this research analyzed eight narrative texts written by students at a private Islamic junior high school in Cirebon. The data were examined using Halliday and Hasan’s (1976) framework, covering six categories of lexical cohesion: repetition, synonymy, antonymy, hyponymy, meronymy, and collocation. The findings revealed 131 occurrences of lexical cohesion, with repetition being the most dominant (105 instances), followed by collocation (8), synonymy (6), hyponymy (6), antonymy (4), and meronymy (2). The results further indicate that students with high achievement students showed a tendency toward a more balanced use of cohesive devices, while low achievement students relied heavily on repetition. These results suggest that the variation and appropriate distribution of lexical cohesion contribute significantly to the overall quality of students’ writing. The study implies that teachers should emphasize the teaching of lexical cohesion to help students develop more coherent, cohesive, and contextually appropriate writing. Future studies are encouraged to include a larger sample and explore other text genres to gain a deeper understanding of students’ lexical cohesion use.